Visit Patterns for Severe Mental Illness with Implementation of Integrated Care: A Pilot Retrospective Cohort Study - Meghan Fondow; Nancy Pandhi; Jason Ricco; Elizabeth Zeidler Schreiter; Lauren Fahey; Neftali Serrano; Marguerite Burns; Elizabeth A. Jacobs (AIMS Public Health, 2015)
There is increasing interest in models that integrate behavioral health services into primary care. For patients with severe mental illness (SMI), a population with disproportionate morbidity and mortality, little is known about the impact of such models on primary care clinic utilization, and provider panels. We performed a retrospective cohort pilot study examining visit patterns for 1,105 patients with SMI overall, by provider, before, and after the implementation of a primary care behavioral health model which had a ramp up period from May 2006-August 2007. We used 2003-2012 electronic health record data from two clinics of a Federally Qualified Health Center and conducted interrupted time series and chi-square analyses. During the intervention period there was a significant increase in the proportion of visits per month to the clinic for patient with SMI relative to overall visits (0.27; 95% CI 0.22-0.32). After the intervention period, this rate declined (-0.23; -0.19-0.28) but remained above the pre-intervention period. After integration of behavioral health into our primary care clinics, there was a sharp increase in the number of patients with SMI, suggesting patient willingness to explore receiving care under this model. Clinics looking to adopt the model should be mindful of potential changes in patient subpopulations and proactively manage this transition.